De novo heterozygous variants in SLC30A7 are a candidate cause for Joubert syndrome. Issue 8 (25th June 2022) - Penon‐Portmann, Monica; Eldomery, Mohammad K.; Potocki, Lorraine; Marafi, Dana; Posey, Jennifer E.; Coban‐Akdemir, Zeynep; Harel, Tamar; Grochowski, Christopher M.; Loucks, Hailey; Devine, Walter Patrick; Van Ziffle, Jessica; Doherty, Dan; et al.
Abstract: Joubert syndrome (JS), a well‐established ciliopathy, is characterized by the distinctive molar tooth sign on brain MRI, ataxia, and neurodevelopmental features. Other manifestations can include polydactyly, accessory frenula, renal, or liver disease. Here, we report individuals meeting criteria for JS with de novo heterozygous variants in SLC30A7 (Chr1p21.2). The first individual is a female with history of unilateral postaxial polydactyly, classic molar tooth sign on MRI, macrocephaly, ataxia, ocular motor apraxia, neurodevelopmental delay, and precocious puberty. Exome sequencing detected a de novo heterozygous missense variant in SLC30A7 : NM_133496.5: c.407 T > C, (p.Val136Ala). The second individual had bilateral postaxial polydactyly, molar tooth sign, macrocephaly, developmental delay, and an extra oral frenulum. A de novo deletion–insertion variant in SLC30A7, c.490_491delinsAG (p.His164Ser) was found. Both de novo variants affect highly conserved residues. Variants were not identified in known Joubert genes for either case. SLC30A7 has not yet been associated with a human phenotype. The SLC30 family of zinc transporters, like SLC30A7, permit cellular efflux of zinc, and although it is expressed in the brain its functions remain unknown. Published data from proteomic studies support SLC30A7 interaction with TCTN3, another protein associated with JS. The potential involvement of such genes in primary cilia suggest a role in Sonic Hedgehog signaling. SLC30A7 is a candidate JS‐associated gene. Future work could be directed toward further characterization of SLC30A7 variants and understanding its function.